Satisfaction With Life Scale (SWLS): Confirmatory Factor Analysis and Psychometrics Properties Among Sample of Nigerian Middle-Aged Workers - Ogunsemi, J. O.; Mopa-Egbunu, A. (Corpus Intellectual, 2024)
Background: The measurement of the cognitive aspect of wellbeing is significant in today’s world due to its link with mental health. The current study examined the factorial structure, psychometric properties and concurrent validity of the Satisfaction with Life Scale (SWLS) within the Nigeria socio-cultural setting. At the initial phase of the study, 109 participants working in a government owned University in Oyo State Nigeria completed the five items SWLS and their information was analyzed utilizing confirmatory factor analysis. One hundred and ten participants from a privately-owned university in Osun State Nigeria was used to concurrently validate the instrument with a similar measure: the six items Riverside Life Satisfaction Scale (RLSS)at the second phase. Result: The SWLS possess a satisfactory reliability (Omega (ωt) = .84). The model fit indicators observed after exposing the SWLS to confirmatory factory analysis revealed moderately suitable fitness and acceptable item loading for a single factor scale. A statistically significant Pearson’s (r) of = 0.79, p<.01 was observed between SWLS and RLSS. The SWLS possess an acceptable psychometrics property. It is a useful instrument for investigating life satisfaction within Nigeria sociocultural contexts.